The Effectiveness Of A Drug Abuse Prevention Module Based On Self-assertiveness, Spirituality And Belief In Thedetriments Of Drug Abuse (mpdask) - Amin Al Haadi Shafie; Durrah Athirah Walid; Abdul Rashid Abdul Aziz; Nurhafizah Mohamad Yassin; Dini Farhana Baharudin; Khatijah Othman; Rafidah Aga Bt Mohd Jaladin; Salleh Amat; Suzaily Wahab (Faculty of Tarbiyah, Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Islamic Guidance and Counseling Journal, Volume 6 Issue 2 Page (1-13)